KEANEKARAGAMAN MAKROFUNGI DI KAWASAN AIR TERJUN KERTA GANGGA KABUPATEN LOMBOK UTARA - Sofiyatur Rahmah (Bioscientiae, 2026)
Although dubbed as a megabiodiversity country, it is currently estimated that the number of fungal species found in Indonesia is around 11,024 species, but there are still many species that have not been properly identified. This study aims to identify several types of macrofungi found in the Kerta Gangga Waterfall Area, North Lombok Regency. Descriptive quantitative research with survey and cruising methods. The results of the study were analyzed quantitatively to calculate the Index of Important Value (INP) as well as several ecological indices. There were 20 species of macrofungi included in 7 orders, 17 families and 19 genus. The species with the highest INP were Penellus stipticus at 26.49 and Coprinopsis lagopus at 25.21, while the species with the lowest INP were Pleurocybella porrigens, Favolus tenuiculus, Cookeina tricholoma and Tubaria furfuracea at 3.37. The results of the calculation of ecological indices which include the abundance index (Di) of 4.09, the Shannon-Wiener diversity index (H') of 2.44 is classified as moderate, the species evenness index (E) of 0.79 is low, Simpson's dominance index (C) of 0.11 is overall low, which is dominated by 2 species, namely Panellus stipticus and Coprinopsis lagopus by 0.03, and the Margalef species richness index (D) of 3.49 which is classified as moderate. Thus, it can be concluded that the ecosystem in the study area is still maintained, characterized by a high level of species richness.